Estimation of actual crop evapotranspiration and supplemental irrigation for Aman rice cultivation in the northern part of Bangladesh - Sen, Rintu; Karim, Nazmun Nahar; Islam, Md Touhidul; Rahman, Mohammed Mizanur; Adham, A K M (Fundamental and Applied Agriculture, 2019)
The study was conducted to estimate the trend of actual crop water require- ment and supplemental irrigation needed for a popular high yielding aman rice variety, i.e., BR11 grown in Rajshahi and Rangpur districts of northern Bangladesh. The FAO Penman-Monteith method was used to estimate the reference crop evapotranspiration (ET0) at four different growth stages of rice. The actual evapotranspiration (ETc) of BR11 rice variety at different growth stages was estimated, and its trend along with that of rainfall was analyzed. The Weibull’s method was employed for performing probability analysis, and the dependable rainfall and ETc at 75% probability level was determined for two different transplanting times and four different growth stages of BR11 for 20 years. It was observed that the rainfall and ETc for the two different transplanting times of BR11 rice varied over the whole growing season in both the districts. After performing the analysis of probability, the supplemental irrigation (SI) was computed for BR11 in both the districts. The study revealed that the SI was required in late-stage for Rajshahi district but, for Rangpur district, it was required in both mid and late stages. The results would be helpful for decision makers as well as for farmers to use water efficiently by understanding the need for ETc and SI for BR11 aman rice cultivation in Bangladesh.